Gladercom freight consignment tracking system - Mutsa, Sharon (Midlands State University, 2019)
The Gladercom Freight Consignment Tracking System is a web based progressive application that allows consigners to book and pay for shipment, and track it till it reaches consignee’s’ destination. The consigner gains access to the system by using login details received via email. The administrator is responsible for viewing paid consignment that is awaiting delivery, drivers that have not been assigned delivery duties and assigning those drivers to deliver consignment. The driver acquires delivery details on the system and after delivery, confirms that consignee has received the goods. The administrator is also responsible for responding to client queries on the system. This system was developed as a result of problems associated with the manual system which are; physical record keeping was cumbersome and led to data loss, long queues for shipment booking and payment, unending phone calls from clients of shipment location, decentralized information sources. Interviews, questionnaires and observations are the information gathering methodologies which were used to acquire information pertaining to the old system. Inhouse development was selected among the evaluated alternatives as it proved to be the most appropriate. The tracking system proved to be feasible after a feasibility study was carried out in these areas, technological, operational, social and economic. The system was developed using PHP, XAMPP, Bootstrap, JavaScript and MySQL. Testing was done through unit testing, integration testing, system testing, acceptance testing, verification and validation, leaving the stem bug free. The system will be mostly maintained using adaptive maintenance, although corrective and perfective maintenance will be used when need arises. In future, there is need to include warehousing and customs clearance on the system so as to improve customer experience and consolidate business processes. Customer suggestions regarding updates should be taken into consideration.